Islamic Law Practice among East Javanesse Chinese Muslims; PITI’s Contribution on Its Enforcement - Mahfud, Choirul; Ummu Salamah; Ahmad Hasyim, Mohamad Yusuf; Zalik Nuryana; Lubis, Muhammad Arif Fadhillah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2024)
This qualitative research explores the practice of Islamic law among Chinese Muslims in Indonesia, focusing on the contribution of the Indonesian Chinese Islamic Association, or Persatuan Islam Tionghoa Indonesia (PITI) in East Java in three aspects; translating the Qur’an into Mandarin, organizing marriage guidance and religious consultation, and facilitating ḥalāl food industry. The primary data collection method involves in-depth interviews with Islamic leaders within the community, particularly those affiliated with PITI. Secondary data is gathered through an extensive review of literature comprising documents, books, news, and articles related to Islamic law practices among Indonesian Chinese Muslims. Data analysis employs a spiral approach, encompassing content analysis, contextual examination, and critical evaluation. The results of this research show that, specifically, PITI East Java is focused on three areas: arranging marriage counseling, translating the Qur'an into Mandarin, and developing a mentoring program for ḥalāl products. Besides, PITI uses a cultural approach to help Chinese Muslims comprehend and follow Islamic precepts while also taking into account their unique background and characteristics. As a result, the Chinese heritage has been influenced by Indonesian and Islamic traditions. This practice is dynamic and still proceeding in the new horizon that needs support from all stakeholders, the government, and other Muslim communities in Indonesia.